Locomotion strategies for amphibious robots-a review - Rafeeq, Mohammed; Toha @ Tohara, Siti Fauziah; Ahmad, Salmiah; Razib, Mohd Asyraf (IEEE, 2021)
In the past two decades, unmanned amphibious robots have proven the most promising and efcient systems ranging from scientic, military, and commercial applications. The applications like monitoring, surveillance, reconnaissance, and military combat operations require platforms to maneuver on challenging, complex, rugged terrains and diverse environments. The recent technological advancements and development in aquatic robotics and mobile robotics have facilitated a more agile, robust, and efcient amphibious robots maneuvering in multiple environments and various terrain proles. Amphibious robot locomotion inspired by nature, such as amphibians, offers augmented exibility, improved adaptability, and higher mobility over terrestrial, aquatic, and aerial mediums. In this review, amphibious robots' locomotion mechanism designed and developed previously are consolidated, systematically The review also analyzes the literature on amphibious robot highlighting the limitations, open research areas, recent key development in this research eld. Further development and contributions to amphibious robot locomotion, actuation, and control can be utilized to perform specic missions in sophisticated environments, where tasks are unsafe or hardly feasible for the divers or traditional aquatic and terrestrial robots.